A Dual-Tracer Method for Differentiating Transendothelial Transport from Paracellular Leakage in Vivo and in Vitro - Muradashvili, Nino; Tyagi, Reeta; Lominadze, David (Frontiers in Physiology, 2012)
Inflammation-induced impaired function of vascular endothelium may cause leakage of plasma proteins that can lead to edema. Proteins may leave the vascular lumen through two main paracellular and transcellular pathways. As the first involves endothelial cell (EC) junction proteins and the second caveolae formation, these two pathways are interconnected. Therefore, it is difficult to differentiate the prevailing role of one or the other pathway during pathology that causes inflammation. Here we present a newly developed dual-tracer probing method that allows differentiation of transcellular from paracellular transport during pathology. This fluorescence-based method can be used in vitro to test changes in EC layer permeability and in vivo in various animal vascular preparations. The method is based on comparison of low molecular weight molecule (LMWM) transport to that of high molecular weight molecule (HMWM) transport through the EC layer or the vascular wall during physiological and pathological conditions. Since the LMWM will leak through mainly the paracellular and HMWM will move through paracellular (when gaps between the ECs are wide enough) and transcellular pathways, the difference in transport rate (during normal conditions and pathology) of these molecules will indicate the prevailing transport pathway involved in overall protein crossing of vascular wall. Thus, the novel approach of assessing the transport kinetics of different size tracers in vivo by intravital microscopy can clarify questions related to identification of target pathways for drug delivery during various pathologies associated with elevated microvascular permeability.